Non-Hodgkin's lymphoma of parotid gland camouflaging as sialadenitis: A case report - Sudharani Biradar; Tanvy Sansgiri; Anita Munde; Basawaraj Biradar (Wolters Kluwer Medknow Publications, 2023)
Non-Hodgkin lymphomas (NHLs) commonly show extranodal involvement (20-30%). Primary diffuse large B-cell lymphomas (DLBCLs) with extranodal localization represent clinically and molecularly distinct entities. Here, we present a case of DLBCL affecting the parotid gland that initially seemed to be sialadenitis. The magnetic resonance Imaging (MRI) and positron emission tomography (PET) scans showed a neoplastic mass in the parotid gland and involvement of the spleen, respectively. The immunohistochemistry (IHC) confirmed the diagnosis of DLBCL. The patient was treated successfully with chemotherapy. A high degree of skepticism is involved in an early diagnosis of NHL as it can mimic benign and malignant entities.